Hysteroscopic findings in infertile women: A retrospective study - Ahmed M. El Huseiny; Badeea S. Soliman (Middle East Fertility Society Journal, 2013)
Background: Lower pregnancy rates are observed in patients with uterine cavity anomalies. The correction of these anomalies has been associated with improved pregnancy rates. Diagnostic hysteroscopy can be performed in an office with minimal discomfort and superior sensitivity and specificity in evaluation of the uterine cavity. Our study was done to evaluate the importance of office hysteroscopy (OH) in diagnosis of pathology among infertile women. Objective: To study incidence of abnormal hysteroscopic findings among infertile women. Materials and Methods: We retrospectively studied 432 office hysteroscopies in patients referred to our unit because of their infertility problem. Two hundred and seventy-four patients (63.43%) were with primary infertility and 158 (36.57%) were with secondary infertility. Results: Normal hysteroscopic findings were reported in 344 women (79.63%). The other 88 (20.37%) were with abnormal hysteroscopy. The most common reported hysteroscopic abnormality was intrauterine adhesions (IUA) 31.81% (28/88) followed by endometrial polyp 26.13% (23/88). Pre-hysteroscopic uterine investigations (ultrasound or hysterography) were available, only, in 207 women. In 143 patients with normal pre-hysteroscopic uterine investigations, office hysteroscopy revealed uterine cavity abnormalities in 21 women (14.68%). Of those with abnormal pre-hysteroscopic findings, 64 patients, hysteroscopy examinations were normal in 16 patients (25%). Conclusions: Office hysteroscopy should be a part of routine work up in infertile patients as routine uterine investigatory methods (ultrasonography and hysterography) have only sensitivity and specificity value of 67.19% and 85.31% respectively.